Antioxidants Contents of Terminalia catappa (Combretaceae) Almonds Grown in Côte d’Ivoire - Douati Togba Etienne; Kouame Kouakou Ahou Christelle; Nyamien Yves; Konan Constant; Coulibaly Adama; Sidibe Daouda; Konan N’guessan Ysidor; Biego Godi Henri Marius (Archives of Current Research International, 2018)
Aims: To determine the antioxidants contents of almonds from fruits of Terminalia catappa L. (Combretaceae) grown in Côte d’Ivoire. Study Design: The almonds of T. catappa were removed from the dried mature fruits harvested in different regions of Côte d’Ivoire. A pool of almonds was drawn at Laboratory and the antioxidants components were determined. Place and Duration of Study: Laboratory of Biochemistry and Food Sciences, Biochemistry department of Biosciences Unit, Félix Houphouet-Boigny University, between October and December 2015. Methodology: The dry fruits of T. catappa were opened using nutcracker. The extracted almonds were oven dried, crushed, put into polyethylene bags, and then kept into a desiccator till analyses. The antioxidant component assessed were phenolic compounds (polyphenol, flavonoid), vitamins (ß-carotene and E), minerals (Fe, Zn, Mn and Cu) and polyunsatured fatty acids (linoleic and linolenic acids). The antioxidant activity was also determined. Results: The results showed that the content of total polyphenol and total flavonoid varies from 1.05 to 7.28 g EAG/l, 0.25 to 0.5g EQ/l. Vitamins ß-carotene and vitamin E were revealed with 1.25±0.06 ER/100g and 1.19±0.12 µg/100g respectively. The sample also revealed means of 7.66±0.21 mg/100g Fe, 0.96±0.32 mg/100g Zn, 13.6±0.5 mg/100g Cu, 0.05±0.002 mg/100g Se and 6.84±0.17 mg/100g Mn. The unsaturated fatty acids profile showed linoleic and linolenic acids with respective rates of 33.29±0.7% and 0.91±0.07%. Finally the antioxidant activity was 2.22 mg/l. Conclusion: The almonds of T. catappa and their unsaturated oil are very good sources of phenolic compounds and interesting mineral and vitamin nutrients for human body as useful dietary supplements and good health.